The Model of Tafsir al-Jalalayn Interpretation on Social Media: A Study of the Qur'anic Concept of Sustenance (Rizq) on the YouTube Channel of KH. Musta'in Syafi'i" - Assia Assia; Wiwin Anis Rohtih; M. Mukhid Mashuri; Nyoko Adi Kuswoyo (Ibn Abbas : Jurnal Ilmu Alquran dan Tafsir, 2026)
It show that the interpretation model used tends to be ijtihadi-contemporary,where KH., Musta’in Syafi’i  not only reads the text of the book but also provides an expansion of meaning. The purpose of the research is to analyze the understanding of the qur’an and examine the contextualization form of classical interpretation social media based on the Tafsir Jalalain as conveyed on the Youtube channel of KH., Musta’in Syafi’i. method the interpretation of jalalain which is ijmali (global) was developed by KH., Musta’in Syafi’i to become a more dynamic model of interpretation of pesantren science in the digital space. Results the researcher used primary data obtained from the Youtube chanel KH. Musta’in Syafi’i took content that officially broadcast his recitation and secondary including the book Tafsir Jalalain  by imam jajaludin al mahalli and jalaludin as suyuti as a text interpreted by the research subject, repetition in the form of books, scientific journals, theses, or articles that discuss the concept of sustenance in the Quran, tafsir methodology, and social media communication theory. Conclusion research to reveal the interpretation model of jalalain tafsir which was originally classic to modern on the KH. Youtube channel Musta’in syafi'i.